Vascular anomalies - Luísa Ciucci Biagioni (Hospital de Clínicas de Itajubá, 2022)
Vascular anomalies are complex diseases with different clinical presentations. In ancient times, some purplish spots were already seen as a curse, and over the centuries, they began to be described as part of other diseases, gaining different eponyms. In recent decades, the term "hemangioma" has been missused to describe a large part of vascular anomalies, causing a significant problem in diagnosing and treating patients.